2013
DOI: 10.1097/prs.0b013e31828bd3b3
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized Groin Lymph Node Flap Transfer for Postmastectomy Upper Limb Lymphedema

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
268
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 300 publications
(282 citation statements)
references
References 43 publications
6
268
1
7
Order By: Relevance
“…The exact mechanism for the effectiveness of VLNT is unclear but is thought to be related to the release of axillary scarring, the reconnection of transplanted and donor site lymphatics, and also a direct pumping/fluid removal of the excess lymph by the transferred lymph nodes. 23 In this series, patients treated for the fluid phase of lymphedema with VLNT had a greater reduction than with LVA in the number of hours of daily garment use and lymphedema therapy required. One explanation for the superior results of VLNT may be that most of the LVA patients were treated for lower extremity lymphedema, whereas VLNT patients all had upper extremity lymphedema.…”
Section: Discussionmentioning
confidence: 91%
“…The exact mechanism for the effectiveness of VLNT is unclear but is thought to be related to the release of axillary scarring, the reconnection of transplanted and donor site lymphatics, and also a direct pumping/fluid removal of the excess lymph by the transferred lymph nodes. 23 In this series, patients treated for the fluid phase of lymphedema with VLNT had a greater reduction than with LVA in the number of hours of daily garment use and lymphedema therapy required. One explanation for the superior results of VLNT may be that most of the LVA patients were treated for lower extremity lymphedema, whereas VLNT patients all had upper extremity lymphedema.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, flap transfer with lymph nodes has been used in the treatment of lymphedema patients [5,6,41,42]. In clinical studies, the LN seems to improve lymphatic flow of the affected arm [5e7].…”
Section: Discussionmentioning
confidence: 99%
“…The superficial inguinal lymph nodes are fed by the SCIA, SIEA, and the medial artery [4]. Recent studies have shown that nodes in the inferior-medial and the central areas of the saphenofemoral junction should not be selected as donor sites for VLNT, because they are the primary superficial nodes draining the lower limb [2,3].…”
Section: Discussionmentioning
confidence: 99%